Pengaruh Current Ratio (CR), Debt of Equity Ratio (DER) dan Net Profit Margin (NPM) Terhadap Harga Saham Pada Perusahaan sub sektor Konstruksi Bangunan yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Tanaya, Eka Prasetya; Amanda, Safa; Megawati, Liya (Jurnal Ilmiah Wahana Pendidikan, 2024)
The capital market plays an important role in the country's economy, one of which is to obtain sources of funds and optimize the allocation of economic resources. An investor must have the ability to understand future capital market conditions when making investment decisions. The construction sub-sector company's share price movement looks quite volatile and tends to decline. There are several factors that can affect stock movements such as the Current Ratio, Debt Equity of Ratio and Net Profit Margin. The method used in this research is descriptive verification method and uses a quantitative approach. The aim is to provide clarity for research with the support of data analysis and literature studies in the form of figures that have been collected. Current Ratio and Net Profit Margin do not partially affect the stock price while the Debt Equity of Ratio partially affects the stock price. the CR, DER, and NPM variables affect the dependent variable, namely the stock price of 61.9%. While the remaining 38.1% is influenced by other factors not examined. The company must make more efforts to improve the financial condition of the company which has a significant role and impact on its share price, so that it can attract investors to invest in the company.